2020
DOI: 10.1177/0300060520941347
|View full text |Cite
|
Sign up to set email alerts
|

Association between ABC family variants rs1800977, rs4149313, and rs1128503 and susceptibility to type 2 diabetes in a Chinese Han population

Abstract: Objective To investigate the association between three single nucleotide polymorphisms (SNPs) of the ATP-binding cassette (ABC) gene family and susceptibility to type 2 diabetes mellitus in a Chinese Han population. Methods A total of 1086 type 2 diabetes patients and 1122 healthy controls were included in this retrospective study. Three genetic variants, rs1800977 and rs4149313 in ABCA1, and rs1128503 in ABCB1 were included in the study. Susceptibility to type 2 diabetes was evaluated under three genetic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Of these studies, 169 studies were excluded for the following reasons: data were on other polymorphisms ( n = 73); there was no ABCA1 polymorphism-grouped lipid outcome ( n = 52); there was no lipid outcome ( n = 19); the study was not a clinical trial ( n = 10); the sample size was less than 20 ( n = 8); the study involved children ( n = 4); there was an overlapping cohort ( n = 2); the study was not in English ( n = 1). Therefore, 18 articles were identified for this systematic review [ 13 , 14 , 15 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, 169 studies were excluded for the following reasons: data were on other polymorphisms ( n = 73); there was no ABCA1 polymorphism-grouped lipid outcome ( n = 52); there was no lipid outcome ( n = 19); the study was not a clinical trial ( n = 10); the sample size was less than 20 ( n = 8); the study involved children ( n = 4); there was an overlapping cohort ( n = 2); the study was not in English ( n = 1). Therefore, 18 articles were identified for this systematic review [ 13 , 14 , 15 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…All of these genotypes are likely to impact metformin’s pharmacokinetics. Ruicheng [ 25 ] found no association between the genotypes of rs1128503 in ABCB1 and diabetes risk in the Chinese Han population, adducing its intronic nature and introns’ characteristic function loss during evolution. Llaudó [ 26 ] described the effect of Pgp activity decrease in PMBC through Rho123 efflux among patients with transplanted kidneys receiving immunosuppressants, who were carriers of allele T/T of rs1045642, and therefore called them “low pumpers,” as opposed to C/C and C/T of rs1045642, the “high pumpers”.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that the expression of the ABCB1 gene is altered in different metabolic diseases including diabetes. 45 …”
Section: Discussionmentioning
confidence: 99%